EASE TRANSACTIONS AND PRIVACY SECURITY ON THE DECISION TO REUSE QRIS AS A TOOL OF PAYMENT THROUGH USER EXPERIENCE IN MADIUN CITY - Setiawan, Hendra; Novitasari, Neza (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2024)
This research aims to analyze the use of e-wallets by involving 384 sample respondents. Quantitative methods were used in this research with purposive sampling techniques. Analysis uses Structural Equation Model (SEM) via SmartPLS software version 4.0.0. The research results show that ease of transactions and partial privacy security have a positive and significant influence on user experience. Furthermore, user experience has a strong, positive, and significant influence on reuse decisions. In addition, ease of transaction and privacy security also have a positive and significant influence on reuse decisions through user experience as an intervening variable. This research provides important insight into the factors that influence the decision to reuse the QRIS Mobile Banking feature in Madiun City, as well as observing the importance of user experience in mediating the relationship between ease of transaction and privacy security with the decision to reuse e-wallets.